2014
DOI: 10.1017/s1759078714000610
|View full text |Cite
|
Sign up to set email alerts
|

Design of non-uniform concentric circular antenna arrays with optimal sidelobe level reduction using biogeography-based optimization

Abstract: Design of non-uniform concentric circular antenna arrays with optimal sidelobe level reduction using biogeography-based optimization nihad dib 1 and ashraf sharaqa 2This paper presents the design of non-uniform concentric circular antenna arrays (CCAAs) of isotropic radiators with optimum sidelobe level (SLL) reduction. The biogeography-based optimization (BBO) method is used to determine an optimum set of excitation amplitudes that provide a radiation pattern with optimum SLL reduction with the constraint of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The CCAA has extensive applications in radio systems like direction finding, radar, RF transmission, navigation and underground propagation, etc. A lot of research on CCAA synthesis has been reported in previous studies . A number of heuristic search algorithms like cat swarm optimization (CSO), biogeography‐based optimization (BBO), firefly algorithm (FA), symbiotic organism search (SOS), moth‐flame optimization (MFO) have been employed for the design of CCAA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCAA has extensive applications in radio systems like direction finding, radar, RF transmission, navigation and underground propagation, etc. A lot of research on CCAA synthesis has been reported in previous studies . A number of heuristic search algorithms like cat swarm optimization (CSO), biogeography‐based optimization (BBO), firefly algorithm (FA), symbiotic organism search (SOS), moth‐flame optimization (MFO) have been employed for the design of CCAA.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research on CCAA synthesis has been reported in previous studies . A number of heuristic search algorithms like cat swarm optimization (CSO), biogeography‐based optimization (BBO), firefly algorithm (FA), symbiotic organism search (SOS), moth‐flame optimization (MFO) have been employed for the design of CCAA. Various heuristic search evolutionary algorithm techniques are also used in the different fields of engineering and system modeling for the solution of complex, nonlinear, irregular, and nondifferentiable optimization problems …”
Section: Introductionmentioning
confidence: 99%
“…A performance comparison of different migration models is given in [52,53]. Additionally, the application of BBO to real-world engineering problems (including problems in wireless communications [25,28,[54][55][56][57][58]) is also a growing trend.…”
Section: Discussionmentioning
confidence: 99%
“…The search in the Scopus database yielded 654 papers that refer to BBO from 2007 to May 2016 with 40 papers that use BBO for antenna design from 2009 till today. BBO has been applied to Yagi-Uda design [110] and array synthesis [111][112][113][114][115][116][117]. Additionally a hybrid DE/BBO algorithm has been used for the design of a reconfigurable antenna array with discrete phase shifters in [118].…”
Section: Other Innovative Algorithmsmentioning
confidence: 99%